Treasures new and old: essays in honor of Donald A. Hagner - Hagner, Donald A.; Sweatman, Carl S.; Kvidahl, Clifford B. (GlossaHouse festschrift series, 2017)
Foreword /Craig A. Evans --Preface /Clifford B. Kvidahl,Carl S. Sweatman --Curriculum vitae of Donald A. Hagner --Part 1: Second-Temple Judaism and Jesus --Second Temple Judaism and early Christianity : similarities and differences /Lee Martin McDonald --Was Jesus a zealot? : finding the right context for an ambiguous concept /Craig A. Evans --Jesus the only teacher : further thoughts /Samuel Byrskog --The intercession of Jesus /Peter Stuhlmacher --Part 2: Studies in Matthew's Gospel --Matthean priority : you must be joking /David Wenham --Matthew, Mithras, and Midrash /Craig L. Blomberg --Matthew's christology and Isaiah's servant : a fresh look at a perennial issue /Jeannine K. Brown --Matthew's (portrayal of ) Jesus : a Jewish Messiah in an anti-Semitic gospel? /Richard A. Burridge --The description of faith in the Gospel of Matthew /Roland Deines --Doubtful faith? : why the disciples doubted until the end (Mt 28:17) /Benjamin Schliesser --Part 3: Studies in Paul --The resurgence of the Paul/Mark nexus : a history of scholarship from Volkmar to Crossley /William R, Telforrd --Paul in Rome /Paul Barnett --Righteousness in the Psalms of Solomon and in Paul /Charles Lee Irons --Part 4: Studies in Hebrews --Another look at the warnings in Hebrews : a response to critics /Thomas R. Schreiner --Experiential cultic soteriology and the origins of Hebrews' high priest christology /Scott D. Mackie --Part 5: Interpretation and function of the Bible --Bart Ehrman vs. Robert McIver on oral tradition /Craig S. Keener --Caravaggio as an interpreter of the New Testament /Reidar Havalvik --How should the Bible function in today's church? /James D. G. Dunn.